Multidimensional Wellbeing in Peru - Pontifical Catholic University of Peru, Institute for Human Development of Latin America (2019)
This is the first bulletin of a series of publications of the “Multidimensional Wellbeing in Peru” research project. The aim of this research was to explore 12 dimensions of wellbeing in Peru using a survey representative at the national and subnational level (7 geographical regions) based on a sample of 2,800 male and female respondents aged 18 years old or above.